2015
DOI: 10.1002/adom.201400628
|View full text |Cite
|
Sign up to set email alerts
|

The Fluoride Host: Nucleation, Growth, and Upconversion of Lanthanide‐Doped Nanoparticles

Abstract: The rapid ascent of nanoscience has garnered significant attention in recent years. Much of the interest generated has dealt with the integration of nanoparticles in various applications ranging from automotive and textiles to bioimaging and nanomedicine. In order for the realization of this potential, their synthesis and chemistry need to be thoroughly understood. One particularly interesting class of nanoparticles comprises a lanthanide‐doped inorganic matrix. Due to their physicochemical and optical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
125
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 112 publications
1
125
0
2
Order By: Relevance
“…These two characteristics explain why UCNPs exhibit sharp optical emission, and relatively long lifetime for their excited states (ranging from µs to ms) [43]. Since 4f n transitions are Laporte-forbidden 2 in order to preserve the dipole moment, there is only a small probability of transition, which results in long excited state lifetime [44]. If n represents the number of electrons in 4f orbitals, there are 14 n possible electronic configurations: it explains the rich energy level diagram of lanthanides.…”
Section: Upconversion: Origin and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two characteristics explain why UCNPs exhibit sharp optical emission, and relatively long lifetime for their excited states (ranging from µs to ms) [43]. Since 4f n transitions are Laporte-forbidden 2 in order to preserve the dipole moment, there is only a small probability of transition, which results in long excited state lifetime [44]. If n represents the number of electrons in 4f orbitals, there are 14 n possible electronic configurations: it explains the rich energy level diagram of lanthanides.…”
Section: Upconversion: Origin and Mechanismsmentioning
confidence: 99%
“…Their high efficiency can partly be explained by the choice of the host material. The fluoride host is a material of choice, because it has low lattice phonon energy, which considerably reduces the probability of non-radiative processes [46,44]. Fluoride hosts are also very stable from a chemical viewpoint.…”
Section: Upconversion: Origin and Mechanismsmentioning
confidence: 99%
“…An ideal host must possess high chemical stability, low lattice phonon energies that minimize non-radiative process and maximize radiative emissions, and close lattice matches to the dopant ions. These characteristics are exhibited by highly stable fluorides such as NaYF 4 , NaGdF 4 , LiYF 4 , NaLuF 4 with phonon energies ~350 cm −1 [38]. Renero-Lecuna et al concluded that low-symmetry hosts offer a more highly disorder structures to the emitting ions resulting in a large site distribution.…”
Section: Lanthanide-doped Upconverting Nanomaterials (Ln-ucnps)mentioning
confidence: 99%
“…Similar to other nonlinear optical technologies, the common multiphoton effect has very low efficiency to upconvert the energy of excited photons, as the intermediate levels are virtual [11] . In comparison, lanthanide-doped upconversion nanoparticles (UCNPs) can effectively convert low-energy photons (always infrared light) into ultraviolet, visible, or near-infrared (NIR) photons, owing to their ladderlike system of energy levels [12] . Until now, owing to their high efficiency, the most frequently used UCNPs have been hexagonal β-NaYF 4 nanoparticles (NPs) doped with Yb 3þ ∕RE 3þ (RE ¼ Er, Tm, Ho) [13,14] .…”
mentioning
confidence: 99%